Detection of multi-drug resistant (MDR) Escherichia coli and tet gene prevalence at a pig farm in Kupang , Indonesia - Kallau, Novalino Harold Geoffrey; Wibawan, I Wayan Teguh; Lukman, Denny Widaya; Sudarwanto, Mirnawati Bachrum (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The purpose of this study was to detect the incidence of multi-drug resistant (MDR) and the spread of tet genes that encode tetracycline (TE) resistance in E. coli in pig farms in the city of Kupang, Indonesia. Materials and Methods: Samples of pig feces have been obtained from 96 pig farms in Kupang city, Indonesia. Escherichia coli bacteria were isolated and identified morphologically and biochemically, and finally confirmed by the API test. The disk diffusion method has been used to observe the antibiotic sensitivity effects and has been followed by observing resistant genes encoding TE resistance using the multiplex polymerase chain reaction (m-PCR) method to detect the presence of tet genes such as tet (A), tet (B), tet (C), tet (D), and tet (E), respectively. Results: A total of 82 (85.4%) of E. coli isolates have been found in all pig feces samples obtained from 96 pig farms in Kupang city. This study has shown a high level of antibiotic resistance dominated by erythromycin (85.4%) and cephalothin (58.5%) and followed by several other antibiotics with a percentage below 34.1%. The prevalence of MDR E. coli was 57.3% by showing 39 different patterns. The most common pattern was showed by the Cephalothin-ColistinErythromycin pattern. The resistance of E. coli to TE appears to be related to the presence of tet (A) and tet (E) genes. Conclusion: This study has encouraged the need for public awareness (farmers) of the wise use of antibiotics in preventing the spread of resistant bacteria that can cause health problems in animals and humans. http://doi.org/10.5455/javar.2018.e289